Vaccination coverage and factors associated with adherence to the vaccination schedule in young children of a rural area in Burkina Faso - Kagoné, Moubassira; Yé, Maurice; Nébié, Eric; Sié, Ali; Schoeps, Anja; Becher, Heiko; Müller, Olaf; Fisker, Ane B. (Global health action, 2017)
Background: Vaccination is an important tool for reducing infectious disease morbidity and mortality. In the past, less than 80% of children 12-23 months of age were fully immunized in Burkina Faso. Objectives: To describe coverage and assess factors associated with adherence to the vaccination schedule in rural area Burkina Faso. Methods: The study population was extracted from the Nouna Health and Demographic surveillance system cohort. Data from four rounds of interviews conducted between November 2012 and June 2014 were considered. This study included 4016 children aged 12-23 months. We assessed the effects of several background factors, including sex, factors reflecting access to health care (residence, place of birth), and maternal factors (age, education, marital status), on being fully immunized defined as having received Bacillus Calmette-Guérin (BCG), three doses of diphtheria-tetanus-pertussis and oral polio vaccine, and measles vaccine by 12 months of age. The associations were studied using binomial regression to derive prevalence ratios (PRs) in univariate and multivariate regression models.Results: The full vaccination coverage increased significantly over time (72% in 2012, 79% in 2013, and 81% in 2014, p = 0.003), and the coverage was significantly lower in urban than in rural areas (PR 0.84; 0.80-0.89). Vaccination coverage was neither influenced by sex nor influenced by place of birth or by maternal factors. Conclusion: The study documented a further improvement in full vaccination coverage in Burkina Faso in recent years and better vaccination coverage in rural than in urban areas. The organization of healthcare systems with systematic outreach activities in the rural areas may explain the difference between rural and urban areas.